Analisis Dampak Penggunaan Aplikasi Tiktok terhadap Perkembangan Sosial Emosional Anak Usia Dini - Khoiriyati, Salis; Hakim, Muhammad Nur; SBE, Warniati (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
The rapid growth of technology has led many young children to use mobile phones to watch videos, with TikTok emerging as a popular platform. TikTok videos, as audio-visual media, can influence children's social-emotional development. This study aims to analyze the impact of the TikTok application on the social-emotional development of children aged 5–6 years at RA Miftahul Ulum. Employing a qualitative descriptive method, data were collected through observation, interviews, and documentation. The research subjects included three children (1 boy and 2 girls), with the TikTok application's impact as the object of study. The findings reveal both positive and negative impacts of TikTok videos on children's social-emotional development. On the positive side, TikTok can make children feel entertained, build self-confidence, and facilitate social interactions with peers. However, the negative effects include increased tendencies to imitate inappropriate behaviors seen in TikTok videos, aggressive language, and poor time management. These findings highlight the dual influence of TikTok on children and underscore the need for parental guidance to mitigate its negative effects. This study emphasizes the importance of monitoring children's exposure to digital media to ensure balanced development.